PENGARUH KOMPLEKSITAS TUGAS, TEKANAN KETAATAN DAN KEMAMPUAN KERJA AUDITOR TERHADAP AUDIT JUDGMENT - Faradish, Nabila (Jurnal Ilmiah Mahasiswa FEB, 2018)
The failure of audits over the last few decades has undermined public confidence in auditor's performance. Auditors are judged to be less intimidating when creating judgment in their assignment. Previous research has suggested that there are several factors that can influence auditors in their judgment. This quantitative study aims to examine the effect of task complexity, obedience pressure, and ability on audit judgment. Using purposive sampling, auditors who are working in Public Accounting Firms (KAP) in Malang and Surabaya and registered in the Indonesian Institute of Certified Public Accountants (IAPI) were selected as the sample. From 90 copies of questionnaires, sixty were returned. The hypothesis testing was carried out using Partial Least Square (PLS). The results of this study prove that task complexity and obedience pressure affect audit judgment, but ability does not affect it. The results also show that obedience pressure is the most dominant factor in influencing audit judgment. Kata Kunci : Kompleksitas tugas, tekanan ketaatan, kemampuan kerja, audit judgment.